Assessment of sesquiterpene lactones isolated from Mikania plants species for their potential efficacy against Trypanosoma cruzi and Leishmania sp. - Laura C Laurella; Natacha Cerny; Augusto E Bivona; Andrés Sánchez Alberti; Gustavo Giberti; Emilio L Malchiodi; Virginia S Martino; Cesar A Catalan; María Rosario Alonso; Silvia I Cazorla; Valeria P Sülsen (Public Library of Science (PLoS), 2017)
Four sesquiterpene lactones, mikanolide, deoxymikanolide, dihydromikanolide and scandenolide, were isolated by a bioassay-guided fractionation of Mikania variifolia and Mikania micrantha dichloromethane extracts. Mikanolide and deoxymikanolide were the major compounds in both extracts (2.2% and 0.4% for Mikania variifolia and 21.0% and 6.4% for Mikania micrantha respectively, calculated on extract dry weight). Mikanolide, deoxymikanolide and dihydromikanolide were active against Trypanosoma cruzi epimastigotes (50% inhibitory concentrations of 0.7, 0.08 and 2.5 μg/mL, for each compound respectively). These sesquiterpene lactones were also active against the bloodstream trypomastigotes (50% inhibitory concentrations for each compound were 2.1, 1.5 and 0.3 μg/mL, respectively) and against amastigotes (50% inhibitory concentrations for each compound were 4.5, 6.3 and 8.5 μg/mL, respectively). By contrast, scandenolide was not active on Trypanosoma cruzi. Besides, mikanolide and deoxymikanolide were also active on Leishmania braziliensis promastigotes (50% inhibitory concentrations of 5.1 and 11.5 μg/mL, respectively). The four sesquiterpene lactones were tested for their cytotoxicity on THP 1 cells. Deoxymikanolide presented the highest selectivity index for trypomastigotes (SI = 54) and amastigotes (SI = 12.5). In an in vivo model of Trypanosoma cruzi infection, deoxymikanolide was able to decrease the parasitemia and the weight loss associated to the acute phase of the parasite infection. More importantly, while 100% of control mice died by day 22 after receiving a lethal T. cruzi infection, 70% of deoxymikanolide-treated mice survived. We also observed that this compound increased TNF-α and IL-12 production by macrophages, which could contribute to control T. cruzi infection.